Structure driven immunomodulatory properties of xylo-/arabinoxylo-oligosaccharides and arabinoxylans in RAW264.7 macrophages. (January 2019) - Mendis, Mihiri; Leclerc, Estelle; Reuhs, Bradley L.; Simsek, Senay
Abstract: Cereal derived arabinoxylans (AX) have been shown to possess immunomodulatory properties. However, AX are complex molecules that can exist with different degree of polymerization (DP) and degree of arabinose substitution (DS). We investigated the effect of these structural differences on the immunomodulatory property of xylo-oligosaccharides (XOS), arabinoxylo-oligosaccharides (AXOS) and AX polysaccharides. We investigated the effect of these substrates on RAW264.7 cells with respect to nitric oxide (NO) and TNF-α production. XOS did not display an immunomodulatory activity with respect to NO production except for X3, which decreased NO production compared to control. AXOS which contained arabinose substitution were better capable of decreasing NO production in macrophages. AX polysaccharides on the other hand were inducers of NO production acting as inmmunostimulators. High molecular weight AX polysaccharide (AX H) was immunostimulators with respect to TNF-α production as well. AX H also displayed a dose dependent relationship with TNF-α production in RAW264.7 cells. These results suggest that exploring high molecular weight AX polysaccharides as immunomodulators could be beneficial compared to smaller molecular weight unsubstituted oligosaccharides. Graphical abstract: fx1 Highlights: AXOS were better capable of decreasing NO production compared to XOS. AX polysaccharides were inducers of NO production acting as inmmunostimulators. High molecular weight AX polysaccharide (AX H) showed immunostimulatory properties. AX H showed dose dependent relationship with respect to TNF-α production.